Optimizing Animal Productivity under Heat Stress Conditions Using Conventional and Recent Technologies - Habeeb, Alsaied Alnaimy Mostafa (American International Journal of Multidisciplinary Scientific Research, 2018)
When the animals exposed to the high environmental temperature most of the physiological and biochemical parameters are disturbances. The heat-induced changes in each of thermoregulatory parameters as well as water, protein turnover or balances and hormonal levels may be used for evaluation the animal’s adaptability to hot climate. Detection of such phenomena in the animals could be achieved by different indices. Most of indices which may be used for detecting the heat adaptability in animals are reviewed in this article paper.